Development of thumbprint recognition system by using Matlab / Nor Hamiza Zahar - Zahar, Nor Hamiza (2001)
As the new millennium was entered, security is always a concern in high technology corporations and consequently, there is an increasing need for reliable concrete identification of people. Identification is used almost everything nowadays, from a school student card to a driver's license. These types of identification have served their purposes, but in a world of six billion people, they are slowly started to lose their appeal. This is where biometrics comes in, offering permanent .identification free of any cards or id numbers. With technology on a constant high-rise, the need for accurate identification is very necessary. Identification can be used as a pass to power. Someone that is correctly identified, and therefore accepted, attains certain privileges. In the field of law enforcement, identification is used to weigh a person's guilt. One means of verifying identity is by employing a fingerprint identification system, which reads the thumbprint of an individual and compares it to the personnel records.